Brunei Darussalam : 2022 Article IV Consultation-Press Release; and Staff Report. - International Monetary Fund. Asia and Pacific Dept. (Washington, D.C. : International Monetary Fund, 2022)
After successfully weathering the pandemic in 2020, Brunei was hit by new waves of COVID-19, with case numbers going up significantly and new lockdown measures imposed in H2 2021. Reduced activities in mining and LNG manufacturing, combined with the negative impact of new pandemic variants on domestic services, led to a slowdown in the economy. Real GDP contracted by 1.6 percent in 2021. For 2022, growth is projected to rebound to 1.2 percent, on the back of easing of mobility constraints and a positive terms of trade shock due to surges in O and G prices. Inflation, while remaining relatively low at 2.2 percent at end 2021, has increased in 2022 and pressures are expected to remain elevated in the short term, owing to supply disruptions and higher food and fuel prices. The economy continues to diversify, with double-digit growth of the food/agriculture sector and a new fertilizer sector commencing production. The risks to the outlook are tilted to the downside, due to potential new COVID-19 variants, increased global uncertainty associated with an escalation of the war in Ukraine, monetary tightening from the US and a larger-than-expected growth slowdown in China. On the upside, higher energy prices would further improve the terms of trade and restore fiscal positions in the short term, while partially contributing to build the buffers needed to ensure stronger intergenerational equity. Strong policy actions are needed to boost medium-term growth and foster resilience.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: International Agreements and Observance; International Organizations; Monetary Policy; Brunei Darussalam